On the potential for high‐resolution lidar to improve rainfall interception estimates in forest ecosystems. Issue 8 (1st October 2007) - Roth, Brian E.; Slatton, K Clint; Cohen, Matthew J.
Abstract : Closing the gaps in the water budget of forested ecosystems is a first‐order challenge, with immediate implications for regional water supply, ecosystem function, and landscape biogeochemistry. Rainfall interception by vegetated canopies can be as great as 50% of total rainfall. There is considerable uncertainty in predicting this ecosystem property, which makes it one of the primary constraints in spatial water budgeting. Interception is largely controlled by vertical structure and canopy gaps on a relatively small scale. Emerging remote sensing technologies, such as lidar (light detection and ranging), now offer an unprecedented opportunity to quantify canopy architecture in three dimensions across the landscape. Use of such high‐resolution spatial data, along with improved rainfall interception models, will aid in ecosystem process studies and the development of tools and incentives that could influence land‐use policy and decision making in the future.